Ressourceneffiziente Füge- und Entfügetechnologien: Online-Content zum interaktiven Whitepaper KORESIL - Meschut, Gerson; Gilich, Julian; Chudalla, Nick Andre (Komplexität beherrschen, Kreisläufe schließen : Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper)
Die Transformation der bisher linearen Wirtschaft zu einer Kreislaufwirtschaft und einer möglichst emissionsneutralen Herstellung und Verwendung von Produkten bedarf einer ganzheitlichen Forschung und Entwicklung in allen Bereichen der Prozesskette. Die Fügetechnik gilt dabei als Enabler moderner Hybridstrukturen und ermöglicht die anforderungsgerechte Verbindung artverschiedener Werkstoffe mit unterschiedlichen technisch-wirtschaftlichen Eigenschaftsprofilen. Aktuelle Herausforderungen umfassen das qualitätsgesicherte Fügen bei einer zunehmenden Materialvielfalt aus Primär- und Sekundärwerkstoffen sowie das gezielte Entfügen von Leichtbaustrukturen in Instandsetzungs- oder Recyclingprozessen. Ein weiterer Entwicklungsschwerpunkt liegt auf der menschzentrierten Ausrichtung von Arbeitsprozessen. So können Arbeitskräfte durch eine ergonomische Produktions- und Fügeprozessplanung sowie die Entwicklung und Einbindung prozessbegleitender Mixed-Reality-Technologien gezielt entlastet und dem derzeit zu verzeichnenden Fachkräftemangel effektiv begegnet werden. Das vorliegende Whitepaper zeigt aktuelle Herausforderungen in der Fügetechnik auf, fasst relevante Erkenntnisse und Lösungsansätze aus Industrie und Forschung sowie dem Verbundforschungsvorhaben „Konzepte für die ressourceneffiziente und sichere Produktion von Leichtbaustrukturen“ (KORESIL) zusammen und leitet geeignete Handlungsempfehlungen für die Industrie ab. Diese sollen beteiligten Anwendern strategische Ansätze aufzeigen, um Prozesse ressourceneffizienter und nachhaltiger gestalten zu können.

Effects of various process parameters in the joining process on the squeeze flow of highly viscous thermal interface materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, B.; Wiebicke, F.; Koch, I.; Gude, M. (Welding in the World)
Powertrain concepts incorporating renewable energies are an essential element of the energy revolution and increasingly require efficient manufacturing processes for electronic systems. Particularly, the joining of structures to be thermally coupled, such as the battery modules and the thermal management system (TMS), poses new challenges in process design. Factors that limit the process include the increased density, viscosity, and abrasiveness of thermal pastes as well as the pressure sensitivity of battery modules. The research presented aims to systematically investigate the influences of joining parameters on flow behavior, the formation of air inclusions, and the occurring joining forces to understand and systematically optimize the joining process. Employing a test setup following the Closing-Hele-Shaw-Cell, the influence of specific process parameters on the joining process such as the joining speed, joining gap, application pattern, and temperature was investigated for a silicone- and a polyurethane-based thermally conductive paste. The results indicate a high dependency of both the ensuing joining forces and the flow behavior on the parameters investigated. These insights imply a potential systematic parameter optimization and the specific adaptation of the joining process to improve flow behavior and reduce compressive stresses. This can ensure lower component deformations and qualify the process for the employment of cell types with a higher power density, a reduced encapsulation, and lower stiffness while at the same time improving production rates.

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimentelle und numerische Untersuchung des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Meschut, Gerson; Gilich, Julian; Gude, Maik; Koch, Ilja; Gröger, Benjamin; Wiebicke, Felix

Ressourceneffiziente Fertigung von Leichtbaustrukturen - Weck, Daniel; Müller-Pabel, Michael; Krampitz, Thomas; Hecker, Christine; Selvaggio, Alessandro; Gilich, Julian; Gude, Maik; Lieberwirth, Holger; Tekkaya, A. Erman; Meschut, Gerson (Werkstattstechnik online)
Zur Steigerung der Ressourceneffizienz technischer Komponenten sind neben dem Leichtbau insbesondere neuartige Fertigungstechnologien und Prozessketten mit geschlossenen Stoffkreisläufen von großer Bedeutung. Im Beitrag werden am Beispiel einer Demonstratorstruktur aus hybriden Leichtbauprofilen (Aluminium und faserverstärktes Polyamid) technisch-technologische Lösungsoptionen für die gesamte Prozesskette inklusive des Recyclings vorgestellt und in Pilotversuchen bewertet.

Solvolytically debondable adhesive systems – potentials and challenges for repair and recycling - Gilich, Julian; Kroos, Janika; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)
In the context of decarbonization initiatives, the repairability and recyclability of components have become a major concern in various industrial sectors, particularly for resource-intensive components. The development of innovative bonding and debonding processes that must adhere to the stringent mechanical specifications of the manufacturers and facilitate their efficient disassembly is a major issue faced in the implementation of a sustainable circular economy. Although adhesively bonded joints satisfy the stringent requirements for mechanical performance, they present several challenges during the repair and recycling process. Solvolytically debondable epoxy resin adhesives may be employed to overcome this issue. In this study, we aim to conduct an exploratory feasibility study on the application of such chemical debonding mechanisms within an adhesive bond as well as to systematically analyse and evaluate the suitability of such adhesive systems for various applications. To this end, we employed various thermo-analytical methods and quasi-static tensile tests to characterise the mechanical adhesive and joint properties of two solvolytically debondable adhesive systems. Furthermore, we analysed the debondability of the adhesive joints and evaluated their feasibility in an industrial environment. The results indicate considerable application potential for solvolytically debondable adhesives, along with further development steps currently required.

Comparison of the economic efficiency and sustainability of two debonding processes for structurally bonded sills - Jordan, Alex; Hermelingmeier, Lucas; Gilich, Julian; Meschut, Gerson; De Santis, Marco Sebastian; Schlüter, Alexander (Journal of Advanced Joining Processes)
In light of growing demands for resource efficiency and sustainability in vehicle engineering, the environmentally compatible separation of structural adhesive joints is gaining increasing relevance. This study presents a comparative analysis of two physically based debonding methods: the established hot-air process and a cryogenic cold process based on liquid nitrogen (LN2). The primary objective is to assess the ecological impact and process-related sustainability of both approaches. Experimental investigations were conducted on a component-representative triple-sheet structure that simulates common automotive flange joints. Thermal input was applied either by convective heating using a hot air gun or by direct cooling through a contact-based LN2 tool. The resulting temperature profiles were recorded using spatially distributed thermocouples. Subsequently, the outer panel was selectively debonded to replicate a repair scenario, and the mechanical integrity of the remaining adhesive joint was evaluated through Mode I testing of L-shaped specimens. Process data served as input for an Life Cycle Assessment (LCA) according to DIN EN ISO 14040. The cryogenic method achieved a 40% reduction in carbon footprint compared to the hot-air process (0.337 kg vs. 0.559 kg CO2-equivalents), primarily due to its shorter process time and more efficient heat transfer. While the hot-air method’s impact is mainly driven by electrical energy use, that of the cold method stems from cryogenic media consumption. Notwithstanding certain disadvantages in specific impact categories, the LN2-based process exhibits a superior overall ecological performance and signifies a promising solution for repair- and recycling-oriented adhesive separation in structural vehicle applications.
Keywords: Sustainable debonding; Structural adhesives; Sustainable joining technologies; Life Cycle Assessment (LCA); Automotive repair process; Economically efficient debonding

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (14. Doktorandenseminar Klebtechnik)

Influences on the Material Displacement and Compression Stresses in the Joining Process of Highly Viscous Thermal Interface Materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (77th IIW Annual Assembly and International Conference on Welding and Joining)

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Influences on the Flow Behavior of Highly Viscous Thermal Interface Materials in the Joining Process - Gilich, Julian; Meschut, Gerson; Wiebicke, Felix; Gröger, Benjamin; Kuhtz, Moritz; Koch, Ilja; Gude, Maik (14th European Adhesion Conference (EURADH) & 7th World Congress on Adhesion and Related Phenomena (WCARP))